2013
DOI: 10.1371/journal.pone.0080719
|View full text |Cite
|
Sign up to set email alerts
|

Who Needs Cream and Sugar When There Is Eco-Labeling? Taste and Willingness to Pay for “Eco-Friendly” Coffee

Abstract: Participants tasted two cups of coffee, decided which they preferred, and then rated each coffee. They were told (in lure) that one of the cups contained “eco-friendly” coffee while the other did not, although the two cups contained identical coffee. In Experiments 1 and 3, but not in Experiment 2, the participants were also told which cup contained which type of coffee before they tasted. The participants preferred the taste of, and were willing to pay more for, the “eco-friendly” coffee, at least those who s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
138
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 55 publications
18
138
0
7
Order By: Relevance
“…The results suggest a luxury brand effect, echoing previous evidence observed in the field of green consumption. Research has shown that products displayed with a green label were preferred to identical products presented with a regular label: consumers chose them more often, accepted paying more for them, and reported a better flavour (Lee, Shimizu, Kniffin, & Wansink, 2013;Linder et al, 2010;Sörqvist et al, 2013;Sörqvist, Haga, Langeborg Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest a luxury brand effect, echoing previous evidence observed in the field of green consumption. Research has shown that products displayed with a green label were preferred to identical products presented with a regular label: consumers chose them more often, accepted paying more for them, and reported a better flavour (Lee, Shimizu, Kniffin, & Wansink, 2013;Linder et al, 2010;Sörqvist et al, 2013;Sörqvist, Haga, Langeborg Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Here it is interesting to note what a profound effect such beliefs about e.g., brand, organic, or free-range have been shown to have in people's ratings of beer and many other foods/drinks [14][15][16][17]. Crucially, while such beliefs can be elicited by naming, branding, pricing, and even the weight of the bottle or the use of bottle versus can as the packaging format [18,19], they can also be driven by the visual appearance of the beer too.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, consumers consider organic products to be reputable products [6], and they expect organic products to be healthy and environmentally friendly. Sörqvist et al [12] found that even if the ingredients in coffee are the same, subjects exhibited a higher purchase intention and sensory evaluation to one kind of coffee when they were informed that it was organic. This means that consumers have expectations In Study 3 (Figure 2), through an actual taste-evaluating experiment, we investigated whether consumers' attitude toward eco-friendly products can differ according to the level of packaging (appropriate vs. excessive); the importance of using proper packaging material was highlighted.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Therefore, consumers consider organic products to be reputable products [6], and they expect organic products to be healthy and environmentally friendly. Sörqvist et al [12] found that even if the ingredients in coffee are the same, subjects exhibited a higher purchase intention and sensory evaluation to one kind of coffee when they were informed that it was organic. This means that consumers have expectations …”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%